SARS-COV-2 IgG specific antibodies persistence in recovered COVID-19 individuals and its association with severity and time of illness - Abdol Sattar Pagheh; Arash Ziaee; Khadijeh Abrari Romenjan; Fatemeh Rezaei; Babak Bahman; Effat Alamzadeh; Samira Elhamirad; Masood Ziaee (New Microbes and New Infections, 2023)
In order to accurately interpret the immune response to COVID-19, it is critical to know how long serum antibodies to COVID-2 persist. This study aimed to describe the serum IgG responses to SARS-CoV-2 in patients with mild, moderate, and severe COVID-19 infection in Birjand, South Khorasan province, Iran. The study was performed on individuals whose COVID-19 disease was confirmed by RT-PCR and recovered from the disease. After completing the questionnaire, blood samples were collected from 4 different groups based on the time of the test at two, four, six, and eight months' post-recovery. Then, SARS-COV-2 virus-specific IgG nucleocapsid antibody level in patients was measured using the enzyme-linked immunosorbent assay (ELISA). In total, 206 patients (mean age 44.19 ​± ​14.9, 51% man) were included in the survey. Serum prevalence of specific IgG antibodies in patients with mild, moderate, and severe COVID-19 disease was 51.5%, 64% and 78.9%, respectively. Furthermore, serum prevalence of COVID-19 specific IgG antibody level in two, four, six, and eight months after recovery were 80.8, 69.1, 43.2 and 41.8%, respectively (p ​< ​0.05). The multiple logistic regression model showed that the variables of age and the time elapsed after recovery had a significant relationship with the positive antibody test of recovered COVID-19 patients (P ​< ​0.05). But other variables had no significant relationship with the result of antibody test (P ​> ​0.05). In the present report, we attempted to characterize the antibody response against SARS-CoV-2 in patients with mild, moderate, and severe COVID-19, with the aim of better elucidating the humoral immune response after recovery from SARS-CoV-2 infection.